A Review of Behavioral Risk Research with Special Application to Developing Countries - Just, David R. (Washington, DC: World Bank, 2012)
Experimental economics grew out of a desire to produce more powerful tests of decision-making processes, as well as employ a more constructive methodology for generating new behavioral models. This paper studies the behavior regularities of individuals facing decisions involving risk or uncertainty, paying particular attention to the potential applications for production and policy behavior in developing countries. Risk is widely acknowledged as a defining problem of agrarian behavior. This overview provides a deeper understanding of the costs and impacts resulting from that risk.